Haszontalan peregrináció? A külföldi egyetemjárás és a hazai jogi kultúra a 16–17. század fordulója körüli időszakban - P. Szabó, Béla (Studia Litteraria, 2026)
This study aims to provide a brief overview of the efforts made in recent decades to identify Hungarian and Transylvanian law students who visited Western European universities in the early modern time to uncover data related to their university stays and studies. Who were those who wasted their time and their own and their patrons’ money on acquiring “useless” legal knowledge at universities? “Useless” because, according to our current knowledge, there was presumably a huge gap between practical legal life, especially in private law relations in Hungary and Transylvania, and the legal thinking imbued with the European ius commune that could be acquired at universities. Those who attended foreign universities probably constituted only a negligible proportion of our legal scholars at the time. Another question is whether this numerical inferiority was not necessarily proportional to the “scientific” and possible practical influence of this group on the legal life of the time. Focusing primarily on the hundred years around the turn of the 16th and 17th centuries, the study aims to provide some insight into the possible impact of legal knowledge acquired at foreign law schools on domestic “legal scholarship,” based on visitation data and on legal and political disputationes, defended at the universities.